Way to happines - "Hubbard,L.Ron" (Los Angeles, 2007)
Few individuals would argue the fact that we live in a noisy, dangerous and somewhat angry society. Individuals looking for answers and solutions to the many problems of mankind often find themselves turning to the wrong solutions $1 (Blike drugs, crime and fighting. Luckily, there are better and more workable solutions, as outlined in The Way to Happiness. The Way to Happiness is a moral code based entirely on common sense. It was originally published in 1981 with the purpose of reversing moral decline and helping to restore integrity, trust and happiness among all mankind. It was written by educator and humanitarian L. Ron Hubbard, and contains twenty-one basic principles that, when applied, can guide an individual into living a much higher quality of life. These principles, make up a code of conduct that can be followed by anyone, no matter their race, colour or creed, and they have the power to repair and strengthen the bonds between all mankind. In addition to being easily grasped and immediately applicable to every individual who reads it, The Way to Happiness holds a Guinness World Record as the single most translated non-religious book ever published. It holds great power, as those who have read it recognises that their actions affect the lives of everyone around them just as much as the actions of others around them affect their own lives. In this way, The Way to Happiness has a ripple effect, spreading its communication of kindness, compassion and respect to more and more individuals in the society as each individual shares its principles with those they care about around them. s
Keywords: Scientology